HUBUNGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF DAN RIWAYAT BERAT BADAN LAHIR BAYI DENGAN KEJADIAN STUNTING PADA BALITA USIA 1-5 TAHUN DI WILAYAH KERJA UPT PUSKESMAS TAMBANG - Putri Rahmadani; Erika Erika; Shinta Dewi Kasih Bratha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Stunting is a condition of chronic malnutrition caused by insufficient nutritional intake over a long period of time due to the provision of food that does not meet nutritional needs. The purpose of this study is to determine the relationship between the history of exclusive breastfeeding and the history of infant birth weight with the incidence of stunting in toddlers aged 1-5 years in the working area of the UPT Tambang Health Center. The sampling technique in this study used Total sampling which had 69 respondents, Data collection tools were questionnaires and observation sheets with analysis using the Fisher's Exact Test with α = 0.05. The results of this study found that there was a relationship between the history of exclusive breastfeeding with the incidence of stunting in toddlers aged 1-5 years in the working area of the UPT Tambang Health Center with a P Value of 0.000, and there was a relationship between the history of infant birth weight with the incidence of stunting in toddlers aged 1-5 in the working area of the UPT Tambang Health Center with a P Value of 0.001. It is suggested that future researchers who are interested in conducting research on the relationship between the history of exclusive breastfeeding and the history of infant birth weight with the incidence of stunting can try to compare the variables that have been studied with other variables that will be studiedKeywords: History of breastfeeding, History of infant birth weight, Stunting